Effect of sympathomimetic compounds with Β-adrenergic effects on plasma free fatty acids in man - T.R.E. Pilkington; R.D. Lowe; R. Foster; B.F. Robinson; A. Antonis (Journal of Lipid Research, 1966)
Nine sympathomimetic compounds were infused intravenously in man, and their effects on the level of plasma free fatty acids, pulse rate, and blood pressure were recorded. Each compound raised the level of plasma free fatty acids. Its activity in this respect could be correlated with its activity in producing Β-adrenergic effects on the circulation; both effects were abolished by pretreatment with propranolol. It is concluded that sympathomimetic compounds that stimulate Β-receptors will raise the plasma concentration of free fatty acids.